Penatalaksanaan Fisioterapi Pada Carpal Tunnel Syndrome Bilateral Di Rumkital Dr. Ramelan Surabaya - Saifudin Ansori, Yusuf; , Dwi Rosella Komala Sari, S.Fis. M.Fis (2015)
Background: Carpal tunnel syndrome is a condition in which the median nerve in the carpal tunnel suppression (carpal tunnel) that would cause a disturbance of pain in wrist, the tingling that radiates to the fingers 1, 2, 3 and 4, the hand feels numb , atrophy of the muscles thenar, decreased muscle strength and decreased functional activity at hand. Objective: To investigate the implementation of physiotherapy in reducing pain, reducing parasthesia, increase muscle strength and range of motion in the case of Carpal Tunnel Syndrome with modalities ultrasound, TENS and Exercise Therapy. Results: After treatment for six times showed a decrease in pain on the right hand silent pain T0: 2, becomes T6: 1, tenderness T0: 4, into T6: 2, pain motion T0: 5, became T6: 4, whereas for left hand silent pain T0: 3, became T6: 1, tenderness T0: 4, became T6: 1, painful motion T0: 5, became T6: 3. Power of the flexor muscles of the right hand wrist T0: 4, became T6: 5 , wrist extensor T0: 5, became T6: 5, ulnar deviation T0: 5, became T6: 5, radial deviation T0: 4, became T6: 5, for the left hand wrist flexor T0: 4, became T6: 5, wrist extensor T0: 5, became T6: 5, ulnar deviation T0: 4, became T6: 4, radial deviation T0: 4, became T6: 4. Scope of the right wrist joint motion T0: S: 50 ° - 0-50 °, into T6 : S: 50 ° - 0-60 °, T0: F: 20 ° - 0-30 °, into T6: F: 20 ° - 0-30 °, while the left hand T0: S: 50 ° - 0-50 °, becomes T6: S: 50 ° - 0-60 °, T0: F: 20 ° - 0-30 °, into T6: F: 20 ° - 0-30 °. Conclusion: Ultrasound can reduce pain and tissue adhesions, provides sedative and relaxing effect improves blood circulation, and exercise therapy (hold relax) increase muscle strength and functional activity of the hand in the case of bilateral CTS.